Fuzzy and Artificial Neural Networks-Based Intelligent Control Systems Using Python - B. Rahmat; B. Nugroho (Future Science)
This research proposes intelligent system programming based on Fuzzy and Artificial Neural Networks (ANN). Programming is built using the Python Programming Language. The control system is used based on Proportional Integral Derivative (PID) Controller, where the gain tuning uses Fuzzy and ANN. The research stages include the preparation of plant models, fuzzy and ANN programming libraries using Python. And then how to show the performance of the Intelligent Control System that was built in the form of a simulation.